Producing democracy in armed violence settings: Elections and citizenship in Eastern DRC. Issue 2 (3rd April 2022) - Vlassenroot, Koen; Nyenyezi, Aymar; Mudinga, Emery Mushagalusa; Muzalia, Godefroid
ABSTRACT: The article analyses how the 2018 in the Democratic Republic of Congo (DRC) contributed to a further opening up of the democratic space and shared expressions and sentiments of citizenship. Through an ethnography of the electoral process in the South Kivu province, we investigate how claiming rights that come with citizenship and how people's political identity, shape and are being shaped by electoral processes. We introduce the notion of citoyenneté to capture the dynamic process of civic political mobilization and positioning. In the case of the DRC, the concept of citoyenneté encapsulates the ideas, positions and actions giving meaning to citizenship and refers both to a formal ideology of nation building and political hegemony; and to an ideology of resistance, guiding acts and strategies to claim rights. We look at the substantive aspect of citoyenneté, or the processes of transformation and re-ownership of the content of citizenship during moments of intensified political competition and change. This process, as we argue, confirms that citizenship is above all a social construction, guiding social behaviour that varies according to the demands being formed around the acquisition of new rights, the redefinition of the political community, existing power competitions and social grievances.